Hybrid nanostructures based on titanium dioxide for enhanced photocatalysis - Reddy, Kakarla Raghava; Hassan, Mahbub; Gomes, Vincent G. (Applied catalysis. A, General, 2015)
•Suitable polymers/nanocarbons with TiO2 enhance photocatalytic activity.•Efficiency depends on morphology, surface area, composition and band gap.•TiO2/PANI or graphene provide outstanding photocatalytic performance. The design and development of efficient TiO2-based, hybrid, nanostructured photocatalysts has recently been receiving substantial attention for environmental remediation due to their excellent physiochemical properties. This article provides an overview of the synthesis strategies and characteristics of the next-generation TiO2-based hybrid photocatalysts, produced in combination with polymers (e.g., polyaniline, polypyrrole, polythiophene) and carbon nanomaterials (e.g., graphene, GO, CNT, carbon quantum dots, carbon nitride). The structural aspects, nanostructure formation process, parameters affecting catalytic activity, photocatalytic mechanisms and photocatalytic applications of TiO2-based catalysts for efficient photocatalytic degradation of gaseous/volatile organic pollutants in water/air are reviewed. Further, current research trends, means to increase catalytic performance and future prospects of high-performance TiO2-based hybrid photocatalytic materials, are briefly summarized.